Persepsi Kepercayaan, Kegunaan, Kemudahan Penggunaan, Keamanan dan Minat Ulang Menggunakan Mobile Banking Jenius - Gita, Ni Wayan; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 31 No 8 (2021)DO - 10.24843/EJA.2021.v31.i08.p16, 2021)
This study aims to determine the effect of perceived trust, usability, ease of use, and security on re-interest in using Jenius mobile banking. This study uses a non-probability sampling method with a purposive sampling technique. The number of samples used in this study were 145 respondents with criteria as Jenius mobile banking users and willing to become respondents. The analysis technique used is multiple linear regression analysis with the help of IBM SPSS Statistics 25 software. Based on the analysis, it is found that the perception of trust has a positive effect on re-interest in using Jenius mobile banking. Usability perception has a positive effect on re-interest in using Jenius mobile banking. Perceived ease of use has no effect on re-interest in using Jenius mobile banking. Perception of security has a positive effect on re-interest in using the Jenius mobile banking. Keywords: Trust; Usefulness ; Ease of Use; Security;  Re-interest.